VERBAL AND VISUAL SIGNS OF BRAND LOGO DESIGNS IN SOME FAST FOOD’S ADVERTISEMENTS: A SEMIOTIC STUDY - Tina Merlina (Universitas Nurtanio Bandung, 2020)
ABSTRACT This research investigates the signs of brand logo designs which occured in some fast food’s advertisements. This is a qualitative research. The researcher takes the data from the advertisement in the internet. To identify the verbal and visual signs of brand logo designs for fast food’s advertisements , the writer analyzed the data using Ekman (2003) . From the discussions, there are verbal and nonverbal signs of brand logo designs that appear in fast food’s advertisements. The meaning of verbal sign and nonverbal sign in “Mc Donald’s” logo design represents joyful. The meaning of verbal sign and nonverbal sign in “Burger King” logo design represent excitement and professional, “SUBWAY” logo design represents enjoyable, purity, and refreshment, “KFC” and “Wendy’s” logo designs represent enjoyable, purity, and passionate. For future researchs need to be conducted with an increased sample by using another brand logo designs such as luxurious brand, perfume, and many more. Keywords: Logo, Fast Food’s, Brand